Studi Bibliometrik Riset Gap Pada Tren Publikasi Tentang Peran Teknologi Digital Pada Perpustakaan - adi Prasetyo Adi Nugroho (THE LIGHT : Journal of Librarianship and Information Science, 2023)
Academics including librarians need publications in order to develop their knowledge. There are so many uses of digital technology for library services that it leaves little novelty behind. This study aims to observe the research trends of preliminary studies related to digital technology and libraries in papers on the Scopus website. This study uses the bibliometric method for searching and analyzing data. The population was found to be around 2298. Then the population will be eliminated based on several inclusion criteria such as using English, only in the form of articles, and only for the field of social science studies. Samples were obtained around 1598 documents on the Scopus website. The results show that the most recent topic trends regarding the use of digital technology in libraries in 2018. This shows that there are no more papers on digital technology after 2018. In Scopus Paper indexed journals about digital technology, libraries globally have novelty/ high novelty if published in 2022 and beyond. In addition, there is not a single sub-topic related to human resources and their management in the library environment. This study also shows that the United Kingdom (UK) is the affiliate with the most citations, followed by the United States of America (USA), Pakistan and China. While the affiliation with the most papers with the highest citations is the USA.